Pengaruh Income Tax, Tunneling Incentive, Bonus Mechanism Terhadap Transfer Pricing - Efta Widiyah; Dirvi Surya Abbas (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
The purpose of this study was to determine the effect of income tax, tunneling incentive, bonus mechanism on transfer pricing in manufacturing industries listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2017-2021 period. The population of this study includes all publicly traded companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained as many as 25 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results show that income tax and tunneling incentive have a positive effect on transfer pricing, while the bonus mechanism has no effect on transfer pricing.